Analisis Pengaruh Tegangan Permukaan Pada Sistem Mikrofluida - Zega, Berkat; Gea, Gregorius Andi Prasition (CV. SINAR HOWUHOWU, 2025)
Surface tension plays a pivotal role in phenomena occurring at the microscale, particularly within microfluidic systems. This research conducts a comprehensive literature review to analyze the influence of surface tension on various aspects of microfluidics, such as droplet formation, flow in microchannels, and fluid-solid interactions. Diverse methods for measuring surface tension at the microscale are also discussed, along with the associated challenges. Furthermore, this review highlights recent advancements in mathematical modeling to predict fluid behavior in microfluidic systems under the influence of surface tension. The findings of this literature review demonstrate that a profound understanding of surface tension is essential for designing and optimizing microfluidic devices for a wide range of applications, spanning from biomedical to chemical industries.